Faktor Penyebab dan Upaya Penyelesaian Klaster 3 Backlog Pendaftaran Tanah Sistematik Lengkap di Kabupaten Tojo Una-Una, Sulawesi Tengah: - - Irawan, Trio; Nugroho, Tanjung; Supama, Yohanes; Kusmiarto, Kusmiarto; Suhendro, Suhendro; Suharto, Eko; Wulan Titik Andari, Dwi (Kadaster: Journal of Land Information Technology, 2025)
Systematic Complete Land Registration (PTSL) is a national program aimed at accelerating and completing the first-time land registration process simultaneously across Indonesia through the "complete village" concept. All land parcels within a village are measured, followed by clustering based on an analysis of physical and juridical data. This clustering aims to facilitate the handling of each typology of land-related issues. One such cluster is Cluster 3 (K3). The existence of K3 parcels hinders the certificate issuance process. This study aims to identify the characteristics and spatial-temporal distribution of K3 in Tojo Una-Una Regency during the 2018–2023 PTSL period, analyze the causal factors, and examine resolution efforts. The research employs a qualitative method. The results show that K3 consists of two main types: K3.1 and K3.3, with temporal distribution fluctuating between 2018 and 2022. Spatially, K3 distribution is sporadic and found in most PTSL villages. The causes of K3.1 include limited SHAT (land ownership certificate) budget compared to the PBT (parcel mapping) budget, incomplete documents, and the absence of statements regarding outstanding BPHTB/PPh tax obligations. Meanwhile, the causes of K3.3 include limited budget for juridical data collection, instant parcel printing practices, and unclear land ownership. The resolution of K3 is carried out through APBN (state budget) mechanisms by re-designating villages as PTSL targets. However, several challenges hinder the resolution efforts, such as budget limitations, lack of personnel and equipment, and low community participation, resulting in unsatisfactory outcomes. Keywords: Cluster 3 Backlog in PTSL, K3 Distribution Pattern, K3 Causal Factors, K3 Resolution Efforts   INTISARI Pendaftaran Tanah Sistematik Lengkap (PTSL) merupakan program untuk mempercepat dan menuntaskan pendaftaran tanah pertama kali secara serentak di seluruh Indonesia dengan konsep desa lengkap. Semua bidang tanah dalam satu desa diukur, kemudian dilakukan klasterisasi bidang-bidang tersebut berdasarkan kajian data fisik dan data yuridis. Klasterisasi ini untuk memudahkan penanganan pada masing-masing tipologi permasalahan bidang tanah. Salah satu klaster adalah Klaster 3 (K3). Adanya bidang tanah K3 menyebabkan terhambatnya proses penerbitan sertipikat. Tujuan penelitian adalah mengetahui karakteristik dan sebaran K3 di Kabupaten Tojo Una-Una pada rentang PTSL 2018-2023, faktor penyebab, dan upaya penyelesaiannya. Penelitian menggunakan metode kualitatif. Hasil penelitian menunjukkan bahwa K3 mempunyai karakteristik K3.1 dan K3.3, dengan sebaran temporal pada rentang PTSL 2018 – 2022 yang sifatnya fluktuatif. Sebaran spasial K3 bersifat sporadis, terdapat di kebanyakan desa PTSL. Penyebab K3.1 adalah terbatasnya anggaran SHAT dibandingkan anggaran PBT, kurang lengkapnya berkas, dan tidak dibuatnya surat pernyataan BPHTB/PPh terhutang. Penyebab K3.3 adalah terbatasnya anggaran pengumpulan data yuridis, praktik mencetak bidang secara instan, dan tidak jelasnya pemilikan tanah. Penyelesaian K3 menggunakan mekanisme APBN dengan menetapkan kembali desa PTSL. Kendala dalam penyelesaian K3 yaitu keterbatasan anggaran, kurangnya tenaga pelaksana dan peralatan, serta rendahnya partisipasi masyarakat, sehingga hasilnya kurang memuaskan. Kata Kunci: Klaster 3 Backlog PTSL, Pola Sebaran K3, Faktor Penyebab K3, Upaya Penyelesaian K3